BALANCED MANAGEMENT OF STAKEHOLDER RELATIONSHIPS IN THE HEATING SPHERE - Tetiana Momot; Irina Sincheskul; Kseniia Savenko; Karina Bukrieieva (Сучасний стан наукових досліджень та технологій в промисловості, 2019)
The article is devoted to the study of theoretical principles and practical aspects of managing relationships with stakeholders of municipal heating companies. The subject of the study is a set of theoretical, methodological and practical aspects for ensuring balanced management of relations with the stakeholders of municipal heating companies. The purpose of the article is to develop theoretical and methodological provisions and substantiate practical recommendations for ensuring a balanced management of these relationships. Tasks of work: to research and systematize the conceptual apparatus of ensuring the management of relations with the stakeholders of municipal heat companies; to justify the organizational principles of managing these relationships; to offer analytical and applied support for managing them on a balanced scorecard. During the research were used methods: abstract-logical analysis, theoretical generalization, systemic and statistical analysis, systemic and statistical analysis, economic-mathematical methods, graphical method. The paper generalizes the economic characteristics of the activity of district heating utilities and develops the directions of development of relations with stakeholders in the process of reforming the housing and municipal services of Ukraine on the basis of the analysis of the efficiency of the municipal heating companies in developed countries of Europe. Strategic directions for the development of district heating utilities by providing balanced stakeholder relationship management are substantiated. Conclusions. It is proposed to use a balanced scorecard, which allows, based on the evaluation of financial and non-financial indicators of enterprise performance, to identify trends of change of each of four key areas of activity to achieve the goal of MHC in meeting the public needs of consumers, profit for the development of the enterprise, ensure the interests of its employees and their satisfaction economic and social needs based on stakeholder reconciliation.